Man and his destiny - Mutahhari, Martyr Murtada ([S.l.] : CreateSpace Independent Publishing Platform, 1988)
This book is one of the many Islamic publications distributed by Ahlulbayt Organization throughout the world in different languages with the aim of conveying the message of Islam to the people of the world. You may read this book carefully and should you be interested to have further study on such publications you can contact us through www.shia.es Naturally, if we find you to be a keen and energetic reader we shall give you a deserving response in sending you some other publications of this Organization.